2020
DOI: 10.1111/tpj.15063
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3K27 dimethylation landscapes contribute to genome stability and genetic recombination during wheat polyploidization

Abstract: SUMMARY Bread wheat (Triticum aestivum) is an allohexaploid that was formed via two allopolyploidization events. Growing evidence suggests histone modifications are involved in the response to ‘genomic shock’ and environmental adaptation during polyploid formation and evolution. However, the role of histone modifications, especially histone H3 lysine‐27 dimethylation (H3K27me2), in genome evolution remains elusive. Here we analyzed H3K27me2 and H3K27me3 profiles in hexaploid wheat and its tetraploid and diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 93 publications
2
18
0
Order By: Relevance
“…We found that 70.9-88.3% of triad genes can maintain their histone modification patterns in the process of domestication and evolution under cultivation at both tetraploid and hexaploid levels. This broadly accords with a recent study that analyzed profiles of two histone methylation markers, H3K27me2 and H3K27me3, in natural tetraploid and hexaploid wheats, and found that while H3K27me2 was affected by ploidy levels, H3K27me3 was largely not [54]. However, slightly different from observations by this study [54], we found small proportions of triad genes bearing modifications by both H3K4me3 and H3K27me3 markers to the A and B subgenomes have undergone further changes at the hexaploid level, but H3K4me3 is more stable than H3K27me3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that 70.9-88.3% of triad genes can maintain their histone modification patterns in the process of domestication and evolution under cultivation at both tetraploid and hexaploid levels. This broadly accords with a recent study that analyzed profiles of two histone methylation markers, H3K27me2 and H3K27me3, in natural tetraploid and hexaploid wheats, and found that while H3K27me2 was affected by ploidy levels, H3K27me3 was largely not [54]. However, slightly different from observations by this study [54], we found small proportions of triad genes bearing modifications by both H3K4me3 and H3K27me3 markers to the A and B subgenomes have undergone further changes at the hexaploid level, but H3K4me3 is more stable than H3K27me3.…”
Section: Discussionsupporting
confidence: 92%
“…This broadly accords with a recent study that analyzed profiles of two histone methylation markers, H3K27me2 and H3K27me3, in natural tetraploid and hexaploid wheats, and found that while H3K27me2 was affected by ploidy levels, H3K27me3 was largely not [54]. However, slightly different from observations by this study [54], we found small proportions of triad genes bearing modifications by both H3K4me3 and H3K27me3 markers to the A and B subgenomes have undergone further changes at the hexaploid level, but H3K4me3 is more stable than H3K27me3. This was reflected by clear differences between ETW (harboring the AABB subgenomes of hexaploid common wheat), and wild tetraploid wheat, T. turgidum ssp.…”
Section: Discussionsupporting
confidence: 92%
“…Under nonstress condition, TEs are repressed in tetraploid rice, leading to reduced CHH methylation. It is also likely that other epigenetic modifications such as histone marks (H3K9me2 and H3K27me2) may repress TE expression, as reported in a recent study on polyploid wheat (53). Hypomethylation in tetraploid wheat after genome separation from hexaploid wheat is reversible after merger with another genome (28).…”
Section: Discussionmentioning
confidence: 86%
“…Large tracts of the crossover-suppressed compartments of the wheat genome are marked by constitutive heterochromatin ( IWGSC 2018 ; Li et al 2019 ; Concia et al 2020 ). Additionally, H3K27me2 associates with crossover suppression in wheat, despite distal enrichment ( Liu et al 2021 ). However, fine-scale relationships between chromatin, meiotic recombination, axis occupancy, and sequence variation in wheat remain incompletely understood.…”
mentioning
confidence: 99%